Caracterización de los desechos sólidos generados en las parroquias (el Chaupi, Aloasí, Alóag, Tambillo) del cantón Mejía, para la elaboración de un plan de manejo. período 2014 - Caizaluisa Caiza, María Esperanza (2014)
Solid wastes are substances or objects generated every day. This cause pollution to the environment, set at human health and ecosystem risks. The present research has the topic: "Characterization of the solid waste which was generated in The Chaupi, Aloasí, Alóag, Tambillo Parishes, Mejía Canton, for the development of a Management Plan”. It is a result a poor management of solid waste generated. The main objective was to characterize the solid waste generated, separate them and quantify them. We got the following results: El Chaupi Parish generates an average of 2481 kilos per day; Aloasí Parish generates an average of 3760 kilos per day; Aloag Parish generates an average of 5776 kilos per day and Tambillo Parish generates an average of 4920 kilos with a total of 16937 kilos per day, equivalent to 0.59 kilograms per capita. According to outcome is elaborated a management plan suitable for the management of solid waste, which includes five programs:1)Institutional strengthening, 2)Training and Environmental education program, 4)Program of collection and transportation, treatment and disposal and monitoring, pursuit and control program.